Comparison of strength and power characteristics before ACL rupture and at the end of rehabilitation before return to sport in professional soccer players - Maestroni, L.; Turner, A.; Papadopoulos, K.; Cohen, D.; Sideris, V.; Graham-Smith, P.; Read, P. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Strength and power is often reduced on the involved versus contralateral limb and healthy controls after anterior cruciate ligament (ACL) reconstruction, but no study has compared with preinjury values at the time of return to sport (RTS).